Attitudes and Opinions of Sports Coaches on the Presence and Interference of Politics in Sports - Ibri Lulzim; Çupi Bajram (Human Research in Rehabilitation, 2024)
The goal of this research is to determine the attitudes and opinions of sports coaches about the presence and interference of politics in sports. The descriptive research method was selected for the problem selected from the quantitative approach. Through 11 questions of the survey, which was built specifically for this research, interesting and expected results were achieved. The survey questionnaire consisted of 3 questions related to socio-status characteristics and 11 questions related to determining the attitudes of sports coaches about the presence and interference of politics in sports. The questionnaire is closed type. Statistical processing of data was done with the program SPSS statistics 25 for the Windows. For the purposes of the research, data was collected and processed on a sample of 125 respondents, male, aged 24 to 62, sports coaches from18 different sports, who perform their duties in 52 different sports clubs in Prizren. Based on the results of this research, it can be concluded that politics is present and interferes in sports. It is inevitable to say thatthe future of sports and athletes depends and will depend on political will.